Migration and myelination by adult glial cells: reconstructive analysis of tissue culture experiments - Wolf, MK (J Neurosci, 1986)
Adult glia are capable of at least limited myelination of CNS axons. However, it is difficult to quantitate their myelination or migratory capacities and to examine contributions of the CNS environment or exogenous factors that might promote or inhibit this process in situ. We have therefore developed a mouse tissue culture system in which optic nerve glia (in the form of appropriately handled optic nerve) are added to chemically demyelinated cerebellar axons. Optic nerve up to postnatal day 411 (P411) contains cells that can migrate out of the nerve into the cerebellar explant and form myelin around its axons. The success rate for myelin formation in these cultures is 57% for immature (P7–11) glia and 55% for adult (P50–411) glia. Computer-generated reconstructions of cultures containing immature (P8) and adult (P89 and P139) nerves demonstrate that in all 3 cases the glia may migrate more than 0.6 mm before myelinating axons, assuming the shortest possible track. Both the age limit for myelination and distance limit for migration, if any, remain to be determined for these adult glia. In successful cultures, myelin always directly abuts the optic nerve surface, whether or not it also extends further, suggesting that migrating glia may depend upon contact guidance by myelin-receptive axons. We conclude that this culture system is a useful model of adult CNS myelin regeneration, in which one can examine the influence of potential trophic or toxic factors on specific aspects of myelinating glial cell behavior.